Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kesejahteraan Keluarga Menggunakan Algoritma C4.5 - Permatasari, Kurnia Ika, Yusuf Sulistyo Nugroho,S.T.,M.Eng (2016)
Poverty is a social phenomenon, not only in developing countries but also in developed countries. Based on data from the Bureau of Statistics Center 2015, in the period of 2009 until - March 2015 poverty among Indonesia's population reached 28.59 million. It proves that there are still many factors that must be addressed from every family that causes poverty. The objective of this study is to help families and governments in predicting welfare level in terms of economic as well as to determine the most influence factor their welfare levels using an application. C4.5 algorithm is used to find the highest gain ratio of the attributes used in this study, such as grains, tubers, fish / shrimp / squid / shellfish, meat, eggs and milk, vegetables, nuts, fruits, oils and coconut, beverage ingredients, spices, other consumables, food and beverages, cigarettes, housing and household facilities, miscellaneous goods and services, clothing, footwear and headgear, durable goods, tax levies and insurance, the purpose of the party / ceremony / festivity, and income. The result of this study is an application used to predict the welfare level of the family and provide the information of influencing factors in accordance with the attributes. So that may be a consideration for families and governments in their future economic planning.